Avaliação sensorial de vinagre de kombucha (Medusomyces gisevii) - Souza, Rosângela Aparecida de (2023)
Kombucha is a fermented drink made from tea, usually green (Camellia sinensis), sugar or honey, added from a symbiotic colony of yeasts and bacteria. Because it is a drink with nutritional properties and high concentration of organic acids, especially acetic acid, Kombucha is promising for the development of vinegar through its fermentation for several weeks or months. The objective of this work was to develop three different samples of acetic fermented from Kombucha of green tea, hibiscus tea and green tea with pineapple pulp, sweetened with honey bee Apis mellifera. The Kombucha was fermented for 45 days, in sterilized glass bottles, at room temperature (summer season) until acidity as close as possible to vinegar. The physicochemical analyzes were performed in the newly prepared Kombucha and during the fermentation time (at time zero, 15, 30 and 45 days) and ash content in the samples only at the final time (45 days). The pH measurements of the samples at time zero and at time final were: FAKA 3.67 and 2.66, FAKH 2.70 and 2.40 and FAKCV 3.12 and 2.34; total acidity in acetic acid (g/100ml): FAKA 0,12 e TF 2,77, FAKH 0,13 e TF 1,81 e FAKCV 0,09 e TF 1,02; ºBRIX: FAKA 6,50 e TF 2,50, FAKH 5,86 e TF 4,00 e FAKCV 6,13 e 4,50; teor de cinzas (g/100mL) no tempo final (45º dia): FAKA 0,04, FAKH 0,04 e FAKCV 0,02 e teor alcoólico % no tempo final: FAKA 0,28, FAKH 0,27 e FAKCV 0,27. The analyzes of E.coli and Salmonella were performed only in the final time with 45 days and the results were negative. The samples were evaluated sensorially through the collaboration of 60 untrained evaluators, aged between 18 and 65 years. The results were submitted to analysis of variance and Tukey test (p <0,05). De um modo geral, pode-se afirmar por meio do teste de aceitação que o vinagre de kombucha de chá verde apresentou maior aceitação em relação ao aroma e sabor e o fermentado acético de kombucha de hibisco melhor aceitação em relação ao atributo cor. Dos 60 provadores, 30 selecionaram a formulação de vinagre de kombucha de chá verde como sua preferência, 19 o vinagre de hibisco e 11 selecionaram o de chá verde com abacaxi. Diante do estudo, foi possível obter produtos com características sensoriais de vinagre aos consumidores, quais declararam boa aceitação do produto. Assim, a kombucha apresentou-se promissora para a produção de vinagre provenientes do chá verde e de hibisco, adoçados com mel, com potencial para comercialização.